Evaluation of Skin Prick Test Results in Textile Workers - Konuk, Suat; Tug, Tuncer (Archives of Clinical and Biomedical Research, 2018)
Objective: Factors such as genetic susceptibility, climate, humidity, vegetation, altitude affect the development of allergy. Exposure to these factors may create allergic related problems in an individual. Based on this we are planning to determine the allergic sensitivity of textile workers in Düzce province of Turkey. Methods: The files of 1142 patients with respiratory allergic disease complaints referred to the pulmonology department in Düzce between April 2014 and January 2017 were retrospectively reviewed. Among those referred to pulmonology examination, there were factory workers coming for periodical controls on the grounds of the agreement protocol with occupational health and safety center and workplace medicine center. This study was planned taking into consideration the textile workers who came for the periodical examination or spontaneously applied. After the restrospective examination of 1142 patient files with respiratory allergic disease complaints, 117 were textile workers among these patients were separately evaluated retrospectively. Skin prick test results were evaluated according to age and sex in textile workers. Results: Of the 117 patients who worked as textile workers, 75 (64.1%) were males and 42 (35.9%) were females. The most frequent reaction was found against D. farinea with 19 patients (16.2%). Other common reactions were found in 15 patients (12.8%) against D. pteronyssinus, 6 patients (5.1%) against grass, 5 patients (4.3%) against grains and 5 patients (4.3%) against grass mixes. Reactions were most frequently detected in the 20-29 age group. Conclusion: Textile workers should be careful especially against house dust mites.